Digital preservation in Indonesia institutional repositories for future community: a literature review - Wardiyono, Wardiyono; Othman, Roslina; Heriyanto, Heriyanto; Mohd Tamrin, Mohd Izzuddin (2024)
In this digital age, academic libraries and repositories have the expertise and the knowledge to manage digital assets. Their digital preservation program will determine the challenge to ensure future access to institutional scientific products. This research uses a literature review to determine the status and the difficulties of having a digital preservation program in Indonesian repositories, emphasising academic/university libraries. This research includes a bibliometric analysis for the preliminary findings. The study is based on Scopus as the primary database and uses the Biblioshiny application as the bibliometric analysis tool. A custom database of open-access journals for Library and Information Science was also built to support the literature review of the topics. The finding showed a lack of comprehensible data to definite conclusions about digital preservation practices due to limited publications. While aiming for the mission and achieving the objectives, the repositories were challenged mainly by technical aspects, the organisation and policy, and the sustainability of the resources for future communities.